The Impact of Job Autonomy on Organisational Commitment and Job Satisfaction: Mediating Role of Organisational Culture in Fast Food Industry of Thailand - Chansuchai, Pichamon; Rotjanawasuthorn, Sippaphat; Jermsittiparsert, Kittisak (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: The aim of this study was to analyse the mediating role of organisational culture in determining the relationship between job autonomy with job satisfaction and job commitment to fast-food restaurants in Thailand. Design/Method/Approach: Quantitative method and primary data were collected from 386 waiters and employees of fast-food restaurants. The questionnaire was distributed in 6 to 7 restaurants and was given to 450 employees but only 386 managed to fill. The independent construct was Job autonomy, mediating was organizational culture and dependent variables were job satisfaction and organisational commitment. SEM has been used as the statistical technique for determining the direct, indirect and mediating effect. Findings: The findings have revealed that there is a significant relationship between job satisfaction, organisational commitment and job autonomy. Organisational culture partially mediated the relationship between the independent and dependent variables. Practical Implications: This study can be applied in the fast-food industry of Thailand to increase employee engagement, motivation and autonomy by participating them in decision making.